ʿAlī-nāma : Manẓūma-ī kuhan (facsimile) - Rabīʿ, (Miras Maktoob, ISBN: 9789004365452., 2019)
Until the discovery of the Persian ʿAlī-nāma , Ibn Ḥusām's Khawarān-nāma (completed in 830/1427) was believed to be the oldest Persian epic poem involving the often wondrous exploits of ʿAlī b. Abī Ṭālib and the beginnings of Shīʿism. The Khawarān-nāma takes its inspiration from Firdawsī's Shāh-nāma (completed in 400/1010), but then adapted to fit the Shīʿī theme, with ʿAlī and his companions often taking the place of Rustam and other heroes. With this facsimile edition of the ʿAlī-nāma we now have access to a much older poem on this subject. Composed by someone using the alias of Rabīʿ, it was completed in 482/1089 in Khurāsān, most probably in or near the town of Sabzawār, just seventy years after the completion of Firdawsī's Shāh-nāma . The text is important because long before others, it acknowledges the heroes of the Shāh-nāma , some of whom were actually written into the script.